2012
DOI: 10.5187/jast.2012.54.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Whole Crop Barley Silage- or Whole Crop Rye Silage based-TMR and Duration of TMR Feeding on Growth, Feed Cost and Meat Characteristics of Hanwoo Steers

Abstract: Feeding trial was conducted with 80 Hanwoo steers (7.5 months of age, 204.4 kg body weight) for 680 days from growing period to late fattening period to examine the feeding value of whole crop barley silage TMR (BS-TMR) and whole crop rye silage TMR (RS-TMR) on body gain, feed cost, slaughter characteristics and quality characteristics of longissimus dorsi muscle. Dietary treatments were conventional separate feeding of concentrate and rice straw (control), feeding BS TMR up to middle fattening period and same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…Thus, daily weight gain was not different across the different treatment groups. These results are in accordance with reports by Jin et al [ 15 ] and Chang et al [ 16 ], wherein there was a difference in feed intake between TMR-based feeding and SCF during the growing period; however, there was no significant difference in body weight gain. Kim et al [ 17 ] argued that compared with SCF feeding, feeding TMR or TMR with fermented feed during the growing period increased daily weight gain, as nutrient use efficiency was improved with fermentation in the rumen.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, daily weight gain was not different across the different treatment groups. These results are in accordance with reports by Jin et al [ 15 ] and Chang et al [ 16 ], wherein there was a difference in feed intake between TMR-based feeding and SCF during the growing period; however, there was no significant difference in body weight gain. Kim et al [ 17 ] argued that compared with SCF feeding, feeding TMR or TMR with fermented feed during the growing period increased daily weight gain, as nutrient use efficiency was improved with fermentation in the rumen.…”
Section: Resultssupporting
confidence: 93%
“…Cho et al [ 8 ] observed lower carcass weight after TMR feeding for 10 months during the late fattening period than that of the SCF group. In contrast, Jin et al [ 15 ] reported that feeding barley silage-based- or rye silage-based-TMR from the growing to late fattening period resulted in higher carcass weight than the SCF group. Our results are in accordance with the findings of Cho et al [ 8 ].…”
Section: Resultsmentioning
confidence: 96%
“…In addition, the late fattening period is the stage where the meat quality is completed; thus, setting the TDN level of concentrate during this period is more effective than setting it during the growing and early fattening periods (Kim, 2015). Increasing the TDN level in concentrate influences the increase in DM degradability and energy availability (Ki, 2009), increases the DMI (Chung et al, 2015), and improves ADG (Jin et al, 2012). However, in the present study, there was no improvement in ADG and FCR with increasing TDN levels in concentrate, and it was found to be most effective at the quantities in the T2.…”
Section: Resultsmentioning
confidence: 99%
“…Barley or ryegrass TMR was not differ in meat quality and meat yield of Hanwoo steers compared with Hanwoo steers fed concentrate diet (Jin et al, 2012). To increase TDN in TMR, It must be added fat source as a supplemented energy.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al (2012) reported that it is possible to use late fattening period of Hanwoo steer with TMR.…”
Section: Introductionmentioning
confidence: 99%